Landing kinematics after ACL reconstruction; do the biomechanist and physiotherapist see different things? - Janssen, I.; van Hunen, M.; Tijssen, M. (ISBS Proceedings Archive (Michigan), 2023)
Rehabilitation following ACL reconstruction is a long process where the chance of a recurrent injury remains high. Compensatory and asymmetric landing strategies, which may lead to these re-injuries, often remain present during the rehabilitation process although not often visually identified. Therefore, the purpose of this study was to compare the visually identified asymmetries with objective inertial sensor data during the Single and Triple Hop test. The kinematic data was able to identify asymmetric kinematics that led to altered strategies that were not identified subjectively by the physiotherapist in both the Single and Triple Hop, in particular in the hip joint. It is speculated that being able to able to identify these asymmetric strategies will improve ACLR rehabilitation and reduce the chance of a re-injury.